Investing in human resource planning: An international study - Erik Døving; Odd Nordhaug (Management Revue, 2010)
In this paper we study drivers of firms' human resource planning practices. This is done by analyzing two central parts of personnel planning, formal HRM strategies and analyses of competence development needs. Data collected from 3,877 firms in 21 countries are applied in the analysis. Nine out of ten firms conduct analyses of needs for competence development to some extent, while every second firm in the sample has elaborated a formal HRM strategy. Results indicate that resources (size, having an HRM department and corporate affiliation) and to some degree cost-benefit considerations are the main determinants of these human resource planning arrangements. Moreover, institutional factors have an impact on firms' use of competence needs analyses.
Keywords: 650; human resource planning; HRM practices; strategy